2018 IEEE Global Engineering Education Conference (EDUCON) 2018
DOI: 10.1109/educon.2018.8363464
|View full text |Cite
|
Sign up to set email alerts
|

Creating engaging experiences in MOOCs through in-course redeemable rewards

Abstract: Gamification strategies have been proposed to mitigate student disengagement and dropouts in massive online environments, due to the positive results shown by these strategies at lower scales. Among various gamification strategies, redeemable rewards have been identified as an effective element to intrinsically motivate students and increase their engagement in educational settings, including MOOCs. Yet, effective design, implementation and enactment of this gamification strategy in MOOC contexts might face ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…Previous studies in small scale educational contexts have shown the benefits of using reward strategies in improving learners' motivation [16,19], engagement [15,21,30,45], learning outcomes [16,30], and enjoyment [19]. However, MOOCs have specific features different from other educational environments (e.g., face to face or blended courses) which may have significant implications in how reward-based gamification strategies affect students [46].…”
Section: Related Workmentioning
confidence: 99%
“…Previous studies in small scale educational contexts have shown the benefits of using reward strategies in improving learners' motivation [16,19], engagement [15,21,30,45], learning outcomes [16,30], and enjoyment [19]. However, MOOCs have specific features different from other educational environments (e.g., face to face or blended courses) which may have significant implications in how reward-based gamification strategies affect students [46].…”
Section: Related Workmentioning
confidence: 99%
“…Badges are optional rewards, represented with graphical icons and issued when users satisfy predefined requirements typically associated with non-compulsory activities (Domínguez et al, 2013;Hamari, 2017). Redeemable Rewards are rewards which provide students with a certain privilege during course runtime (e.g., extra attempts in quizzes, access to extra content, join a queue to receive feedback from teachers) (O'Donovan et al, 2013;Ortega-Arranz et al, 2018). These two reward types have been also positively evaluated by students in other MOOC studies (Cross et al, 2014;Rizzardini et al, 2016).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The gamification was digitally represented and implemented with an extended version of the GamiTool portal 6 . GamiTool is a web-based system developed by the authors that allows instructional designers and teachers to design, and semi-automatically deploy and enact reward-based gamifications in multiple MOOC platforms such as Canvas Network (Ortega-Arranz et al, 2018). GamiTool allows to include a "Rewards" tab in the course interface where students could check the reward conditions and request the badges and redeemable rewards once the conditions were fulfilled.…”
Section: Gamification Implementationmentioning
confidence: 99%
“…As pointed out by several studies (2), (15), (16), (17), only about 10% of the students who enroll in MOOCs actually finish them. Some solutions to this problem include personalizing the students' experience, as suggested by Assami et al (18), or by using a gamification approach, described in the work of Ortega-Arranz et al (19). Lately, however, online courses are shifting to a more controlled environment, in which you can get access to all exercises only if you pay for a certificate.…”
Section: Related Workmentioning
confidence: 99%